Employability skills for hospitality students in Malaysia - Ahmad, Nor Aziah; Kenayathulla, Husaina Banu; Idris, Abdul Rahman (2017)
Malaysia needs high skilled workforce to support growth of the industry. With dynamically changing job market and progressive technological change, employees are expected to keep abreast of global economics. In the process of achieving the status of developed nation by the year 2020, Malaysia needs to restructure its workforce to ensure that middle level workers are highly skilled. Current job environment demands multi-task and skills. Thus, university graduates must be prepared to meet the demand especially in the hospitality industry. The purpose of this study is to identify the level of employability skills in the hospitality field. This research applied quantitative methodology. The respondents consist of final year students in bakery and culinary programme. Stratified sampling was used to select students in hospitality programs from 22 vocational colleges in Malaysia. Questionnaires were distributed to 841 students in five regions which are Central, South, North, East and East Malaysia (Sarawak) in Malaysia. Descriptive analysis was used to analyse the quantitative data. The results showed that the level of hospitality employability skills among vocational students in Malaysia were at high level of competence (93.2%). The research has brought meaningful implications for hospitality vocational students, employers and policy makers.